The Value of Local Content in ELT Materials in Indonesia - Halim Ahmad Faizin; Ita Permatasari; Muhyiddin Aziz (Journal of English Language and Education, 2022)
The new paradigm on the position of English in the world has shifted as now English was no longer the property of native speakers. This shifting paradigm challenge the traditional assumption of English teaching world on whether English teachers should incorporate local or target culture in their teaching materials. This is a qualitative research using critical literature review method. This article provides a discussion about the issue of representation of local content in English teaching materials in Indonesia context. The issue is analysed from various perspectives, they are: world Englishes, English as International Language, culture and identity, materials development and how they shape the idea of how English teaching materials in Indonesia should be developed. Conclusion and a few recommendations about the issue of local content in teaching materials in Indonesia are presented and discussed in the end of the paper.